Strategi Pemenangan Pasangan Calon Herman Deru Dan Mawardi Yahya Pada Pilkada Sumatera Selatan Tahun 2018 - Reni Apriani; Maharani Maharani (Jurnal Studi Sosial dan Politik, 2019)
Election of Regional Heads of South Sumatra Province has been held in 2018 with 4 pairs of candidates participated and won by the couple Herman Deru and Mawardi Yahya. The interesting thing from this research is that there has been intense competition between the four Paslon. Where each candidate, previously served as regional head in several districts in South Sumatra. The victory of this couple did not escape the winning strategy that they have implemented. The problem discussed in this study is how the process of the campaign implemented by Herman Deru and Mawardi Yahya in the South Sumatra Regional Election in 2018 and what the winning strategy used by the Paslon. The researcher uses the strategy theory from Kotten where in this theory it is stated that there are 4 types of winning strategies namely organizational strategy, program strategy, resource strategy, and institutional strategy. This type of research is a qualitative descriptive study. Methods of collecting data from this study through interviews, observation, and documentation. The results of this study indicate that of the 4 types of winning strategies as proposed by Kotten, the four strategies have been implemented by the couple Herman Deru and Mawardi Yahya. The strategy they use is different from the strategies used by other partners such as organizational strategy. Specifically in the program section and how to campaign through social media. And there are 4 stages of the campaign process set by the South Sumatra KPU in the South Sumatra Regional Election in the 2018-2023 period, namely public debates, distribution of campaign materials, installation of campaign props, and campaign advertisements in the media.